A Customized Intervention for Dementia Caregivers: A Quasi-Experimental Design. (August 2019) - Wawrziczny, Emilie; Larochette, Clotilde; Papo, David; Constant, Emilie; Ducharme, Francine; Kergoat, Marie-Jeanne; Pasquier, Florence; Antoine, Pascal
Objective: The aim of this study is to test the effects of a customized intervention on distress among caregivers of persons with dementia (PWD) using a quasi-experimental design.Method: Fifty-one spouse caregivers in the experimental group and 51 in the control group participated in the study. The effects of the intervention were examined by comparing caregivers' responses with questionnaires at pre-intervention baseline (T0) and immediately after intervention (T1). Differences were quantified using repeated-measures ANOVA.Results: The analyses indicated a stabilizing effect of the intervention on caregivers' perceptions of PWD's daily functioning, self-esteem related to caregiving, quality of family support, and feeling of distress. Linear increases were observed regarding sense of preparedness and impact on daily routine, while no differences (interaction and linear effects) were observed for degree of self-efficacy, depression, impact on finances, or self-rated health.Conclusion: These findings show a preliminary efficacy of the intervention proposed in this study to prevent the exacerbation of caregivers' distress.